HUMANITIES EDUCATION AND MILITARY AFFAIRS IN MODERN SCIENTIFIC DISCOURSE - Aleshchenko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article deals with the human education problems, its role and significance for the national identity formation in the context of modern scientific discourse. The basic principles of humanitarian education and its key aspects are covered. It is emphasized that the issues of formation of outlook, Ukrainian identity, civic position, military culture are among the most urgent problems of revival and development of the Ukrainian army.It is determined that humanitarian knowledge is an important component of the higher education system and allows the formation of a person, a citizen and a patriot, not a narrowly trained professional. The role of the humanitarian component in higher education institutions is to call upon not only the transfer of scientific knowledge to the students, but also to form their value orientations and to increase the level of culture.In this context, sound thinking requires calling for the humanitarian component of education as an important factor in social change. There is a discrepancy between the amount of humanitarian knowledge (disciplines) and the possibility of their assimilation within the allotted time; formation of various humanitarian pedagogical practices; continuing to reproduce traditional forms of teaching that have largely exhausted themselves; the humanitarian component of education is poorly responsive to the problems and demands of the present.The terms “hardskills” and “softskills” are described as the core competencies that shape higher education institutions. It is determined that one of the important tasks of today is to train specialists of the new type who have key competences formed at a high level; capable of continuous updating and updating of knowledge; have a good command of foreign languages at a level sufficient for the implementation of quality professional foreign language communication. Modern modular educational technologies should be oriented to the new system of knowledge and will allow their updating and renewal in the conditions of continuous education throughout the officer's service.It is emphasized that the development of a humanistic strategy in military affairs is of great importance in creating a unified space of historical memory and shaping national identity - increasing the teaching of humanitarian disciplines in higher education institutions of the defense forces aimed at training the new type of specialists who have the key competencies of an officer-leader, patriot.It is noted that in military educational institutions of the armies of the leading countries of the world considerable attention is paid to the teaching of the social sciences as a problem of national security. The main ways to increase the effectiveness of the higher military education system of Ukraine in accordance with European requirements have been formed.
Keywords: education, military education, human education, competence, national identity